Microbial generalists as keystone species: constructing core network modules in the anthosphere of twelve diverse wild plant species - Jihoon Kim; Yingshun Cui; Kyong-Hee Nam; Jun-Woo Lee; Jong-Geol Kim; Seong-Jun Chun (Environmental Microbiome)
Abstract Background The anthosphere, also known as the floral microbiome, is a crucial component of the plant reproductive system. Therefore, understanding the anthospheric microbiome is essential to explore the diversity, interactions, and functions of wildflowers that coexist in natural habitats. We aimed to explore microbial interaction mechanisms and key drivers of microbial community structures using 144 flower samples from 12 different wild plant species inhabiting the same natural environment in South Korea. Results The microbial diversity of the anthosphere showed plant dependence, with the highest diversity observed in Forsythia koreana, indicating microbial dynamics in relation to plant species. Caulobacter, Sphingomonas, Achromobacter, Epicoccum, Cladosporium, and Alternaria were anthosphere generalists, suggesting that the local plant anthosphere had a similar microbial composition. Ecological network analysis revealed that anthosphere generalists were tightly coupled to each other and constructed core modules in the anthosphere. Functions associated with parasites and pathogens were commonly observed in the anthosphere, particularly in Capsella bursa-pastoris and Brassica juncea. Conclusion Overall, the anthosphere depends on the plant species and microbial generalists function as keystone species to support and connect the anthospheric microbiome in natural habitats.